2018
DOI: 10.5505/pajes.2017.47108
|View full text |Cite
|
Sign up to set email alerts
|

A simulated annealing approach based simulation-optimisation to the dynamic job-shop scheduling problem

Abstract: ÖzIn this study, we address a production scheduling problem. The scheduling problem is encountered in a job-shop production type. The production system is discrete and dynamic system in which jobs arrive continually. We introduce a simulation model (SM) to identify several situations such as machine failures, changing due dates in which scheduling rules (SRs) should be selected independently. Three SRs, i.e. the earliest due date rule (EDD), the shortest processing time first rule (SPT) and the first in first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They showed that their proposed GRASP-based approach yields viable solutions. Sel and Hamzadayı (2018) [56] proposed a simulation optimization study based on the SA carried out in the DJSP. They considered average flow time and average tardiness as the criteria.…”
Section: Dynamic Problemmentioning
confidence: 99%
“…They showed that their proposed GRASP-based approach yields viable solutions. Sel and Hamzadayı (2018) [56] proposed a simulation optimization study based on the SA carried out in the DJSP. They considered average flow time and average tardiness as the criteria.…”
Section: Dynamic Problemmentioning
confidence: 99%
“…Over the years, many authors have proposed both general and problem-specific improvements and variants of SA [36]. Different variants of scheduling problems have been tackled using SA [37], such as the job-shop scheduling problem [38][39][40][41], university course timetabling problems [42], or sports scheduling problems [43].…”
Section: Simulated Annealing Adaptationmentioning
confidence: 99%
“…They proposed branch population GA for optimization. Sel and Hamzadayi [16] used simulated annealing (SA) for JSSP and used Arena for simulations. Fu et al [17] established a multiobjective optimization model for a JSSP and used NSGA to minimize some performance measurements such as the total cost and the total completion time.…”
Section: Introductionmentioning
confidence: 99%